Peran Instruktur dalam Meningkatkan Keterampilan Warga Belajar Program Pelatihan Instalasi Listrik - Elis, Ros; Santika, Tika (Journal of Nonformal Education and Community Empowerment, 2018)
The background of this research is based on how the role and function of instructors in conducting electrical installation training. The purpose of this research is to analyze the role of instructors and supporting factors in improving the skills of the learnes of electrical installation training program in BLK Kabupaten Karawang. The approach used in this research is qualitative through case study method. Subjects in this study consisted of one organizer, one instructor and five learners. The techniques used in collecting data are observation, interview and documentation study. Research phase is done through orientation, exploration, and member check. The results show that the role of instructors in training, preparing training materials and making final training reports. The instructor is responsible for preparing the training materials, preparing the facilities and evaluating the trainees. Supporting factors of training facilities used such as measurement labs, electrical rating labs and electrical installation assembly labs are in good condition. Motivation of learners after attending the training is to get skills and work in the electrical maintenance department. The motivation of the learners in training is quite high. There is support from families of learners and instructor in every training process. The ability of instructors in electric installation training is professional and trained.